Cosmopolitanism and Identity - Şener, Sami (Journal of History Culture and Art Research, 2014)
Cosmopolitanism and Identity Abstract Cosmopolitism is a complicated concept and has different properties. Pure tangible objects in the world are worth more than those mixed. This character distinguishes objects and gives them a special value. Is the same situation true in the spiritual and moral worlds? Already, every object finds its value in their value world. In particular, this also applies in the real social world in general. Social world has a meaning because of living with others. So, our world enriches with disparateness and this situation adds new values to our life. For this reason It is very importance to know how to keep different cultures together. In general, we mainly reserve a share in a narrow mentality for ourselves. But, when we look to the events from other people's perspectives we discern different realities. Today, we face many chaos and social problems. The cause of it that we could not endure living together with others and do not have toleration culture about different groups. Such a behaviour stems from psychological weakness and keep ourselves in the forefront in ethnical issues. Whereas all great success in the history has been obtained by civilizations and leaders who had understood the differentiations as richness. In this subject culture as life philosophy and value of law are quite important concepts. Most important issues will lead us to success and understanding of law in this issue. With this approach we have to behave most suitable attitude to the life and human being without hegemonic or ethnic perspective.